Cultural Variability in the Attribute Framing Effect - Cheon, Jeong Eun; Nam, Yeseul; Kim, Kaylyn J.; Lee, Hae In; Park, Haeyoung Gideon; Kim, Young-Hoon (Frontiers in Psychology, 2021)
An intriguing phenomenon that arises from decision-making is that the decision maker’s choice is often influenced by whether the option is presented in a positive or negative frame, even though the options are, de facto, identical to one another. Yet, the impact of such differential framing of equivalent information, referred to as the attribute framing effect, may not be the same for every culture; rather, some cultures may be more readily influenced by the differentially valenced frames than others (i.e., showing a greater difference in evaluation in a positive vs. negative frame). The present study investigates to what extent and why cultures may differ in their sensitivity to the attribute framing effect. Participants were recruited from South Korea and the United States, cultures characterized by their focus on prevention and promotion, respectively, to test for the cultural variability in the attribute framing effect. The results revealed that Korean participants were markedly more influenced by the valence of the frame than North American participants. Regulatory focus explained why Koreas showed a greater sensitivity toward the attribute framing effect than North Americans. Specifically, a greater prevention (vs. promotion) orientation of Korean participants led them to show a greater evaluation gap in the positive and negative frames. Implications for cultural significance on the attribute framing effect are discussed.